2020
DOI: 10.1039/c9ra10106c
|View full text |Cite
|
Sign up to set email alerts
|

Heating-up synthesis of cesium bismuth bromide perovskite nanocrystals with tailored composition, morphology, and optical properties

Abstract: Lead-free cesium bismuth bromide perovskite nanocrystals are synthesized via the heating-up method with tailored morphology and optical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…Prior to discharging, two peaks attributed to the BiBr 3 appeared, at 159.9 and 164.8 eV and there was no obvious metallic Bi peak. The peaks attributed to the Bi metal is close to the reported values of the Cs 3 Bi 2 Br 9 (Bi 3+ ) [25] . Following discharging, metallic Bi peaks appeared at 157.0 and 162.2 eV while the intensities of the BiBr 3 peaks were decreased.…”
Section: Properties Cubr2 Febr3 Bibr3 Agbrsupporting
confidence: 84%
See 1 more Smart Citation
“…Prior to discharging, two peaks attributed to the BiBr 3 appeared, at 159.9 and 164.8 eV and there was no obvious metallic Bi peak. The peaks attributed to the Bi metal is close to the reported values of the Cs 3 Bi 2 Br 9 (Bi 3+ ) [25] . Following discharging, metallic Bi peaks appeared at 157.0 and 162.2 eV while the intensities of the BiBr 3 peaks were decreased.…”
Section: Properties Cubr2 Febr3 Bibr3 Agbrsupporting
confidence: 84%
“…The peaks attributed to the Bi metal is close to the reported values of the Cs 3 Bi 2 Br 9 (Bi 3 + ). [25] Following discharging, metallic Bi peaks appeared at 157.0 and 162.2 eV while the intensities of the BiBr 3 peaks were decreased. The peaks attributed to the Bi metal is close to the reported values.…”
mentioning
confidence: 98%
“…Despite the success of Cs 3 Bi 2 X 9 NCs synthesis, the optical performances, especially PLQY, seem to be inferior than that of Pb-based counterparts [138]. Some recent studies in this field have shown that Cs 3 Bi 2 X 9 NCs with high PLQY can be produced through careful manipulation of surface ligands and solvents [139]. For example, Yang and coworkers synthesized Cs 3 Bi 2 X 9 NCs through a ligandfree facile reaction at RT and the resulting Cs 3 Bi 2 Br 9 NCs exhibited a low PLQY (~0.2%) because of the ultrafast trapping process [131].…”
Section: Bi(iii)-mentioning
confidence: 99%
“…Especially materials based on bismuth halides are investigated, because they are expected to be non‐toxic, [2] however, some of them proved to be better suited as luminescent materials [3] . Among the many compounds discussed are alkali metal salts of type M 3 Bi X 6 ( M =Rb, Cs; X =Br, I), which are sometimes referred to as “zero‐dimensional perovskites”, because of their isolated [Bi X 6 ] octahedra, or as “double halide perovskites“ [2–5] …”
Section: Introductionmentioning
confidence: 99%
“…[3] Among the many compounds discussed are alkali metal salts of type M 3 BiX 6 (M = Rb, Cs; X = Br, I), which are sometimes referred to as "zero-dimensional perovskites", because of their isolated [BiX 6 ] octahedra, or as "double halide perovskites". [2][3][4][5] One of the major issues in the application of bismuth halide absorber materials is their inherent tendency to hydrolyze. The binary bismuth trihalides react with liquid or gaseous water to form oxide halides, preferably BiOX.…”
Section: Introductionmentioning
confidence: 99%